The effects of different physiologic concentrations of prolactin in association with reproductive hormones on the incidence of type 2 diabetes mellitus in men: Tehran Lipid and Glucose Study - Atrin Niknam; Fatemeh Mahboobifard; Maryam Rahmati; Faezeh Firouzi; Ehsan Rojhani; Fereidoun Azizi; Fahimeh Ramezani Tehrani (BMC Endocrine Disorders, 2022)
Abstract Background Data is inconsistent and, for the most part, not sufficient to demonstrate the association between serum Prolactin (PRL) concentration within the physiologic range and the incidence rate of type 2 Diabetes Mellitus (DM) among men. Moreover, since both PRL and type 2 DM are associated with reproductive hormones, investigating these hormones might improve our understanding of how PRL might impose its effect on the incidence rate of type 2 DM. Methods For the present study, 652 eligible men aged 29–70 with a normal baseline PRL concentration were selected from the Tehran Lipid and Glucose Study (TLGS). Participants were sub-classified into three groups (tertiles) according to the serum concentration of PRL and were followed for 15.8 years. The incidence of type 2 DM and PRL, LH, FSH, testosterone, and AMH concentrations were measured. The effect of hormonal variables on the incidence of type 2 DM was estimated using the log-binomial model, adjusted for major confounding factors. The correlations between PRL and the indicators of glucose and lipid metabolism and other hormonal variables were also explored. Results In the unadjusted model, PRL was not significantly associated with the incidence rate of type 2 DM (RR = 0.98, 95% CI: 0.94 − 1.03). After adjusting for potential confounders, the inverse effect of AMH on the incidence rate of type 2 DM was the only significant association. The analyses also indicated a significant positive association between PRL and LH/FSH ratio (r = 0.1, P = 0.01). Conclusion No significant association was found between serum PRL concentrations within the physiologic range and the incidence rate of type 2 diabetes mellitus among middle-aged men. Men with higher concentrations of PRL within the physiologic range tended to show higher levels of LH and LH/FSH. AMH was the only variable significantly linked to the incidence rate of type 2 DM in men.